Analisa Metode Strenght Weaknesess Opportunities Threats (SWOT) di Pasaraya Bintan 21 - Vita Rahayu; Resti Daryopi; Fanny Saputra (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2025)
This study aims to analyze the state of Pasaraya Bintan 21 using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) method. This method is used to identify internal and external factors affecting the company’s operations that influence the success of the marketplace in competing in the retail industry. Data were obtained through interviews, observations, and relevant document analysis. The research results show that Pasaraya Bintan 21 has several strengths, such as a strategic location and a diverse range of products, but also faces weaknesses in terms of promotion and innovation. Opportunities for growth are wide open with the increase in population and consumer interest in local products, while threats include intense competition and changing shopping trends.